2015
DOI: 10.7567/apex.9.016201
|View full text |Cite
|
Sign up to set email alerts
|

Simple method of improving harvest by nonthermal air plasma irradiation of seeds of Arabidopsis thaliana (L.)

Abstract: We have studied the effects of air nonthermal plasma irradiation of seeds of Arabidopsis thaliana (L.) on their growth from the beginning of cultivation to their harvest. Three minute plasma irradiation of dry seeds resulted in growth acceleration in all the growth stages. Compared with the control, the plasma irradiation led to an 11% shorter harvest period, a 56% increase in total seed weight, a 12% increase in each seed weight, and a 39% increase in seed number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
90
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 33 publications
3
90
0
Order By: Relevance
“…For example, recent studies by Koga et al . showed that a single 3-minute treatment of dry seeds of Arabidopsis thaliana led to growth acceleration in all the growth stages, including shorter harvest period, a considerable increase in total seed weight, an increase in each seed weight, and a substantial increase in seed number21. Although the specific mechanisms by which plasma-generated physical and chemical effects influence the metabolic activity of the seed or the plant remain poorly understood, changes in morphological and sowing features of seeds11, dehydrogenase activity, superoxide dismutase (SOD) and peroxidase activity, photosynthetic pigments, photosynthetic efficiency and nitrate reductase activity have been reported12.…”
mentioning
confidence: 99%
“…For example, recent studies by Koga et al . showed that a single 3-minute treatment of dry seeds of Arabidopsis thaliana led to growth acceleration in all the growth stages, including shorter harvest period, a considerable increase in total seed weight, an increase in each seed weight, and a substantial increase in seed number21. Although the specific mechanisms by which plasma-generated physical and chemical effects influence the metabolic activity of the seed or the plant remain poorly understood, changes in morphological and sowing features of seeds11, dehydrogenase activity, superoxide dismutase (SOD) and peroxidase activity, photosynthetic pigments, photosynthetic efficiency and nitrate reductase activity have been reported12.…”
mentioning
confidence: 99%
“…It is important to clarify advantages and disadvantages of plasma treatments over other methods. One important advantage of plasma treatments is the fact that highly reactive and short lifetime species of high density without any thermal damage can be provided by plasmas [2][3][4][5][6][7][8][9][10][11][12][13][14]. Highly reactive species are more effective than stable chemicals and have much less residual harmful effects due to their short lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…As one of such approaches using plasmas, we have shown that atmospheric pressure plasma treatments of seeds can boost crop yield, reduce cultivation time and improve agricultural productivity [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Koga et al studied the effects of air nonthermal plasma irradiation on Arabidopsis thaliana seeds and reported that plasma irradiation led to a 12% increase in seed weight and a 39% increase in seed number. 13 Ling et al suggested that cold plasma treatment improves oilseed rape drought tolerance by improving antioxidant enzyme activities, increasing osmotic-adjustment products, and reducing lipid peroxidation, especially in drought-sensitive cultivars. 14 Será et al applied low-pressure discharge to stimulate germination of seeds using a microwave power supply.…”
Section: Introductionmentioning
confidence: 99%